2017
DOI: 10.3390/ijgi7010006
|View full text |Cite
|
Sign up to set email alerts
|

Roadblocks Hindering the Reuse of Open Geodata in Colombia and Spain: A Data User’s Perspective

Abstract: Open data initiatives are playing an important role in current city governments. Despite more data being made open, few studies have looked into barriers to open geographic data reuse from a data consumer's perspective. This article suggests a taxonomy of these barriers for Colombia and Spain, based on a literature review, an online questionnaire, and workshops conducted in four cities of these two countries. The taxonomy highlights that issues such as outdated data, low integration of data producers, publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…This question was addressed in the following way. Initially, a set of barriers were identified to help define a taxonomy to validate what the most critical frictions were regarding the re‐usability level of open geographic data in cities from a data user's perspective (Benitez‐Paez et al, ). Once the obstacles were confirmed, data users were consulted about their concerns and what the priorities should be that any open data initiative requires to enhance its re‐usability level.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This question was addressed in the following way. Initially, a set of barriers were identified to help define a taxonomy to validate what the most critical frictions were regarding the re‐usability level of open geographic data in cities from a data user's perspective (Benitez‐Paez et al, ). Once the obstacles were confirmed, data users were consulted about their concerns and what the priorities should be that any open data initiative requires to enhance its re‐usability level.…”
Section: Methodsmentioning
confidence: 99%
“…(), Welle Donker and van Loenen (), Benitez‐Paez et al. ()Identification of users’ and re‐users’ needsKassen (), Janssen and Zuiderwijk (), Williamson and Eisen (), Benitez‐Paez et al. ()User‐focused metadataComber et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within GIScience, re-use of these datasets has attracted the interest from research, and previous work has suggested, inter alia, semantic application programming interfaces to retrieve datasets according to their thematic categories [16], a platform to monitor open data re-use [14], a one-stop portal for open data search [23], and a vision of intelligent geovisualization to exploit these datasets [15]. Direct and indirect costs of open geospatial data provision were discussed in [29]; Benitez-Paez et al [5] presented an empirically-derived taxonomy of barriers to open data re-use from a user's standpoint; and Benitez-Paez et al [4] proposed a conceptual framework to improve the reusability of open geographic data in cities.…”
Section: Introductionmentioning
confidence: 99%